Preparation method of super-hydrophobic material and super-hydrophobic material
By oxidizing and self-assembling the melted olefin polymer resin and adding polysiloxane, the problem of insufficient performance of polyolefin superhydrophobic materials in the prior art is solved, and the efficient preparation of materials with superhydrophobic properties is achieved.
Patent Information
- Application Number
- CN202510115662.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, when preparing polyolefin-based superhydrophobic materials, it is difficult to achieve superhydrophobic properties, especially the polypropylene materials have insufficient superhydrophobic contact angle, and the superhydrophobic characteristics are not fully realized.
The olefin polymer resin in the molten state was oxidized and dissolved in an organic solvent, and then poured into a poor solvent for precipitation and self-assembly, and obtained a material with superhydrophobic properties. Polysiloxane is added to the olefin polymer resin to further improve the hydrophobic properties.
A superhydrophobic material with a hydrophobic angle of no less than 150° and a rolling angle of no more than 10° is achieved, which simplifies the preparation process, eliminates the need for special equipment, and improves the superhydrophobic properties of the material.
Smart Images

Figure CN119859291A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of super hydrophobic materials and relates to a preparation method of a super hydrophobic material and the super hydrophobic material. Background Art
[0002] Superhydrophobic materials have a surface stable contact angle greater than 150° and a rolling contact angle less than 10°. They are a new type of material that is currently being used in many fields, including anti-fouling, anti-corrosion, and self-cleaning. Superhydrophobic materials need to construct micro-nano structures on their surfaces to prevent water droplets from wetting the surface. There are currently a variety of methods for preparing superhydrophobic materials, including: (1) treating the surface with ultra-low surface tension; (2) constructing micro-nano structures on the surface; (3) a combination of the above two methods. A common preparation method is to use a combination of nanoparticle materials and film-forming materials. The film-forming material forms a film on the surface of the substrate, and the nanoparticle material forms a plurality of protruding micro-nano structures on the film layer. However, this method often requires the film-forming material to have a certain degree of hydrophobicity, or even better hydrophobicity, so that it can be combined to provide a superhydrophobic effect.
[0003] Polyolefin is a commonly used plastic. Document 1 discloses a method for achieving super-hydrophobic modification of polypropylene materials, wherein the polypropylene material is decontaminated and then immersed in a potassium permanganate solution for treatment, and then immersed in a fluorinated acrylate solution for polymerization reaction. The contact angle of the super-hydrophobic polypropylene obtained by this method reaches about 140°, which is not considered super-hydrophobic.
[0004] Document 1: CN115522387A.
[0005] The applicant believes that it is necessary to improve the preparation method of polyolefin-based superhydrophobic materials. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a super-hydrophobic material and a super-hydrophobic material.
[0007] The technical solution of the present invention is as follows:
[0008] A method for preparing a super-hydrophobic material comprises the following steps: molten olefin polymer resin is oxidized and then dissolved in an organic solvent, then poured into a poor solvent for precipitation, and solids are collected and dried to obtain the super-hydrophobic material.
[0009] Preferably, the olefin polymer resin is selected from a homopolymer of one of C2-C8 α-olefins and cycloolefins or a copolymer of two or more thereof.
[0010] Preferably, the oxidant used for the oxidation is selected from one or a combination of two or more of oxygen, ozone, organic peroxides, persulfates, hypochlorites and percarbonates.
[0011] Preferably, the weight ratio of the olefin polymer resin to the organic solvent is 1-20:10.
[0012] Preferably, the organic solvent is selected from one or a combination of two or more of non-polar organic solvents and low-polar organic solvents.
[0013] Preferably, the volume ratio of the organic solvent to the poor solvent is 1:5-50.
[0014] Preferably, the poor solvent is selected from one or a combination of two or more highly polar solvents.
[0015] Preferably, the olefin polymer resin contains 0.5-5% of polysiloxane by weight of the olefin polymer resin.
[0016] More preferably, the structure of the polysiloxane is as shown in the following formula (1):
[0017] R 1 Me2SiO(SiOMe2) x (SiOMeR 2 ) y SiMe2R 3 (1)
[0018] Among them, R 1 , R 2 and R 3 independently selected from C1-C18 alkyl, Me represents methyl, x≥0, y≥0, 5≤x+y≤100.
[0019] A super-hydrophobic material is prepared by the method for preparing the super-hydrophobic material described in any one of the above technical solutions.
[0020] The beneficial effects of the present invention are:
[0021] (1) The present invention adopts a method in which an oxidized olefin polymer resin is self-assembled in a poor solvent to obtain a polyolefin material having super-hydrophobic properties. The preparation method is simple and does not require the use of special equipment.
[0022] (2) In the present invention, polysiloxane material is further added to the olefin polymer resin, and the hydrophobicity of the polysiloxane can be utilized to further improve the superhydrophobic performance of the superhydrophobic material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Attached Figure 1 Schematic diagram of the water drop angle of the superhydrophobic material obtained in Example 1 after being flattened. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is further illustrated and described below through specific implementation methods.
[0025] On the one hand, the present invention provides a method for preparing a super-hydrophobic material, comprising the steps of: oxidizing an olefin polymer resin in a molten state and then dissolving it in an organic solvent, then pouring it into a poor solvent for precipitation, collecting and drying the solid, and obtaining a super-hydrophobic material.
[0026] The polarity of olefin polymer is relatively low and it is not easy to dissolve. The present invention finds that olefin polymer resin can be easily dissolved in an organic solvent after oxidation, and then poured into a poor solvent to precipitate and self-assemble synchronously, thereby forming a material with super-hydrophobic properties of micro-nano structure. If the olefin polymer resin is directly dissolved in an organic solvent and then poured into a poor solvent to precipitate, it may be that the precipitation process cannot self-assemble, and the super-hydrophobic material with micro-nano structure cannot be obtained.
[0027] Olefin polymer resin is solid at room temperature, not easy to oxidize, and oxidation may also be uneven. Using olefin polymer resin in a molten state, oxidation can be carried out more evenly. After oxidation, the main chain of the olefin polymer resin will be broken and oxidized, and the organic groups of the side chains will also be oxidized. The alkyl groups of the side chains or the hydrogen of the main chain will be partially converted into polar groups such as hydroxyl, carboxyl, ketone, etc., not only the molecular weight will be reduced, but also the molecular polarity of the olefin polymer resin will be increased, and it will be easier to dissolve in organic solvents (especially non-polar organic solvents and low-polarity organic solvents). In the present invention, the olefin polymer resin in a molten state can be achieved by heating with a twin-screw extruder, heating with a reactor, etc.
[0028] In a preferred embodiment of the present invention, the olefin polymer resin is selected from a homopolymer of one of C2-C8 α-olefins and cycloolefins or a copolymer of two or more thereof. In the present invention, the α-olefin can be ethylene, propylene, 1-butene, 1-hexene, 1-octene, etc., and the cycloolefin can be cyclobutene, cyclooctene, 1-methylcyclobutene, 3-methylcyclobutene, etc. The olefin polymer resin can be polyethylene, polypropylene, ethylene / 1-butene copolymer, ethylene / 1-octene copolymer, propylene / cyclobutene copolymer, etc. Different olefin polymer resins have different melting temperatures, and the temperature of the olefin polymer resin in the molten state is also different. For example, for polyethylene, the melting temperature can be 190-220°C, for polypropylene, the melting temperature can be 220-250°C, and for ethylene / 1-butene copolymer, the melting temperature can be 160-190°C.
[0029] In a preferred embodiment of the present invention, the oxidant used for oxidation is selected from one or a combination of two or more of oxygen, ozone, organic peroxide, persulfate, hypochlorite and percarbonate. Different oxidants have different oxidizing abilities, and the amount of oxidant used, the oxidation reaction time and the addition method are also different. For gaseous oxidants, such as oxygen and ozone, a method of continuously passing into the molten olefin polymer resin is usually adopted. For liquid and solid oxidants, a method of first mixing with the olefin polymer resin and then melting together is usually adopted. In order to improve the oxidation effect and efficiency, a combination of two or more oxidants can also be adopted to synergistically exert the oxidation performance of two or more oxidants, such as a combination of oxygen and organic peroxide, a combination of oxygen and persulfate, a combination of oxygen and percarbonate, etc. In the present invention, during oxidation, the weight of the added oxidant is not particularly limited, and can be 0.2-5% of the weight of the olefin polymer resin. According to the amount of the oxidant added and the temperature of the oxidation reaction, the time of the oxidation reaction can be adjusted accordingly, such as 0.5-24h. Generally, the higher the oxidation reaction temperature and the more the oxidant added, the shorter the oxidation reaction time. In order to improve the oxidation efficiency, a certain amount of accelerator may be added to the olefin polymer resin, such as benzyl chloride, triphenylmethane, diphenylmethane, etc. The amount of the accelerator may be 20-100% of the amount of the oxidant. For example, the organic peroxide may be diisopropylbenzene peroxide, tert-butyl hydroperoxide, methyl ethyl ketone peroxide, isobutyl methyl ketone peroxide, etc., the persulfate may be ammonium persulfate, sodium persulfate, potassium persulfate, etc., the hypochlorite may be sodium hypochlorite, potassium hypochlorite, etc., and the percarbonate may be ammonium percarbonate, sodium percarbonate, potassium percarbonate, etc.
[0030] In a preferred embodiment of the present invention, the weight ratio of the olefin polymer resin to the organic solvent is 1-20:10. The purpose of adding the organic solvent is mainly to dissolve the oxidized olefin polymer resin and form a solution of the oxidized olefin polymer resin. When the oxidized olefin polymer resin solution is added to the poor solvent, the oxidized olefin polymer resin can self-assemble and precipitate. For example, the weight ratio of the olefin polymer resin to the organic solvent can be any value of 1:10, 3:10, 5:10, 7:10, 8:10, 9:10, 10:10, 11:10, 12:10, 15:10, 17:10, 18:10, 20:10, etc., without special restrictions. Further, the weight ratio of the olefin polymer resin to the organic solvent can be 5-15:10.
[0031] In a preferred embodiment of the present invention, the organic solvent is selected from one or a combination of two or more of non-polar organic solvents and low-polar organic solvents. The dielectric constant of the non-polar organic solvent and the low-polar organic solvent does not exceed 12 at 20°C. Non-polar organic solvents and low-polar organic solvents will not or are difficult to undergo proton self-transfer reaction, and will not undergo solvation with oxidized olefin polymer resins. For example, benzene, toluene, xylene, cyclohexane, petroleum ether, dichloromethane, 1,2-dichloroethane, carbon tetrachloride, etc. More preferably, the dielectric constant of non-polar organic solvents and low-polar organic solvents does not exceed 5 at 20°C, such as toluene, xylene, cyclohexane, n-hexane, petroleum ether, etc. The polarity of the oxidized olefin polymer resin is still relatively low, and the dissolving effect of non-polar organic solvents or low-polar organic solvents as good solvents is better.
[0032] In a preferred embodiment of the present invention, the volume ratio of the organic solvent to the poor solvent is 1:5-50. A sufficient amount of the poor solvent can be conducive to the self-assembly and precipitation of the oxidized olefin polymer resin. For example, the volume ratio of the organic solvent to the poor solvent can be any value of 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, etc., without special restrictions. Further, the volume ratio of the organic solvent to the poor solvent can be 1:10-50.
[0033] In a preferred embodiment of the present invention, the poor solvent is selected from one or a combination of two or more of the high polarity solvents. The high polarity solvent has a dielectric constant of not less than 16 at 20°C and can undergo a proton self-transfer reaction. The polarity of the oxidized olefin polymer resin is still relatively low, and its solubility in the high polarity solvent is relatively poor. The high polarity solvent can be used as a poor solvent for the oxidized olefin polymer resin. For example, the poor solvent can be water, methanol, ethanol, acetone, methyl ethyl ketone, ethylene glycol dimethyl ether, ethylene glycol monomethyl ether, etc.
[0034] In the preferred embodiment of the present invention, the polysiloxane containing 0.5-5% of the weight of the olefin polymer resin is contained in the olefin polymer resin.Polysiloxane has good hydrophobic effect, and good heat resistance, compared with the olefin polymer resin, the possibility of the organic group of the polysiloxane side chain or the hydrogen of the main chain being oxidized is less, and the oxidized polysiloxane may produce partial chemical combination with the olefin polymer resin, and due to the incompatibility or partial incompatibility of polysiloxane with the oxidized olefin polymer resin, therefore can migrate on the surface of the formed super-hydrophobic material when the oxidized olefin polymer resin is precipitated and self-assembled into a super-hydrophobic material, can further reduce the surface energy of the super-hydrophobic material and improve super-hydrophobic performance, such as the hydrophobic angle is larger and the rolling angle is lower.For example, the weight of the polysiloxane can be any value in 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% etc. of the weight of the olefin polymer resin, without particular restrictions.Further, the weight of the polysiloxane can be 1-4% of the weight of the olefin polymer resin.
[0035] In a more preferred embodiment of the present invention, the structure of the polysiloxane is shown in the following formula (1):
[0036] R 1 Me2SiO(SiOMe2) x (SiOMeR 2 ) y SiMe2R 3 (1)
[0037] Among them, R 1 , R 2 and R 3 independently selected from C1-C18 alkyl, Me represents methyl, x≥0, y≥0, 5≤x+y≤100.
[0038] The polysiloxane of the present invention preferably has saturated alkyl groups as side chains and terminal groups, which has better antioxidant properties than olefin polymer resins, and may chemically bond with oxidized olefin polymer resins and maintain good low surface energy performance, which is more conducive to migration to the surface of super-hydrophobic materials during self-assembly in poor solvents and improves the hydrophobic properties of super-hydrophobic materials. In the present invention, when R 1 , R 2 and R 3 It is found that the hydrophobicity of super-hydrophobic materials is more beneficial when they are not methyl groups, which may be due to the fact that R 1 , R 2 and / or R 3 The longer the carbon chain, the worse the antioxidant performance. The oxidized polysiloxane and the oxidized olefin polymer resin are almost completely incompatible to partially incompatible. The more uniformly the oxidized polysiloxane can migrate and precipitate on the surface of the superhydrophobic material, the more beneficial it is to further improve the hydrophobicity.
[0039] On the other hand, the present invention also provides a super hydrophobic material prepared by the method for preparing a super hydrophobic material according to any one of the above technical solutions. The super hydrophobic material of the present invention has a distinct micro-nano structure, a hydrophobic angle of not less than 150°, and a rolling angle of not more than 10°.
[0040] The technical solution of the present invention is further described and illustrated according to various embodiments below.
[0041] Example 1
[0042] The reaction raw materials - 100g polypropylene (230℃, 2.16Kg load, melt index 5g / 10min) and 1g potassium persulfate were added to the reactor, heated to the oxidation reaction temperature of 240℃ under nitrogen protection and stirred for 5h, cooled to no more than 50℃, added 100g toluene, stirred to dissolve evenly, and then slowly poured into 2000g95% ethanol for precipitation, collected the precipitated particles, and dried at 60℃ for 5h to obtain a superhydrophobic material.
[0043] Attached Figure 1 This is a schematic diagram of the hydrophobicity of the super hydrophobic material of this embodiment after being flattened and tested.
[0044] Example 2
[0045] The difference between this embodiment and embodiment 1 is that in embodiment 1, the stirring time of 5 hours is adjusted to 2 hours, and the other steps remain unchanged.
[0046] Example 3
[0047] The difference between this embodiment and embodiment 1 is that in embodiment 1, the stirring time of 5 hours is adjusted to 12 hours, and the other steps remain unchanged.
[0048] Example 4
[0049] The difference between this embodiment and embodiment 2 is that in embodiment 2, the oxidation reaction temperature of 240° C. is adjusted to an oxidation reaction temperature of 280° C. The remaining steps remain unchanged.
[0050] Example 5
[0051] The difference between this embodiment and embodiment 2 is that in embodiment 2, the raw material components further include 0.5 parts of triphenylmethane. The remaining steps remain unchanged.
[0052] Example 6
[0053] The difference between this embodiment and embodiment 1 is that in embodiment 1, 2000 g of 95% ethanol is replaced by a combination of 1600 g of water and 400 g of anhydrous ethanol. The remaining steps remain unchanged.
[0054] Comparative Example 1
[0055] 100 g of the polypropylene in Example 1 was added to a reactor, the temperature was raised to 100° C., 100 g of toluene was added, stirred until uniformly dissolved, 2000 g of 95% ethanol was slowly poured in for precipitation, the precipitated particles were collected, and dried at 60° C. for 5 h to obtain a polypropylene material.
[0056] Example 7
[0057] The raw material components - 100g linear low-density polyethylene (190℃, 2.16Kg load, melt index 2g / 10min), 0.2g diphenylmethane and 0.8g potassium persulfate were added to the reactor, heated to the oxidation reaction temperature of 200℃ and stirred for 8h under nitrogen protection, cooled to no more than 50℃, added 200g toluene, stirred and dissolved evenly, slowly poured into a poor solvent consisting of 1000g water and 2000g anhydrous ethanol for precipitation, collected the precipitated particles, and dried at 60℃ for 12h to obtain a superhydrophobic material.
[0058] Example 8
[0059] The difference between this embodiment and embodiment 7 is that in embodiment 7, the raw material components further include 1g of polysiloxane Me3SiO(SiOMe2) 32.7 SiMe3. The rest of the steps remain the same.
[0060] Example 9
[0061] The difference between this embodiment and embodiment 7 is that in embodiment 7, the raw material component further includes 1 g of polysiloxane. The remaining steps remain unchanged.
[0062] The structure of polysiloxane is: Me3SiO(SiOMe2) 25.2 (SiOMeR 2 ) 8.3 SiMe3, R 2 It is n-butyl.
[0063] Example 10
[0064] The difference between this embodiment and embodiment 9 is that in embodiment 9, the amount of polysiloxane is adjusted from 1 g to 3 g, and the other steps remain unchanged.
[0065] Performance Testing
[0066] Water drop angle: measured using a water contact angle tester.
[0067] Roll angle: tested using the inclined surface method.
[0068] The results are shown in Table 1 below.
[0069] Table 1
[0070]
[0071]
[0072] From the data results in Table 1 above, it can be seen that the present invention can obtain a super-hydrophobic material by oxidizing the olefin polymer resin and then precipitating and self-assembling. Moreover, after further adding a polysiloxane material to the olefin polymer resin, the hydrophobic property of the super-hydrophobic material can be further improved, with a higher water drop angle and a lower rolling angle.
[0073] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a super hydrophobic material, characterized in that: The steps include: molten olefin polymer resin is oxidized and then dissolved in an organic solvent, then poured into a poor solvent for precipitation, solids are collected and dried to obtain the super hydrophobic material.
2. The method for preparing a super hydrophobic material according to claim 1, wherein The olefin polymer resin is selected from a homopolymer of one of C2-C8 α-olefins and cycloolefins or a copolymer of two or more thereof.
3. The method for preparing a super hydrophobic material according to claim 1, wherein The oxidant used for the oxidation is selected from one or a combination of two or more of oxygen, ozone, organic peroxide, persulfate, hypochlorite and percarbonate.
4. The method for preparing a super hydrophobic material according to claim 1, wherein The weight ratio of the olefin polymer resin to the organic solvent is 1-20:
10.
5. The method for preparing a super hydrophobic material according to claim 1, wherein The organic solvent is selected from one or a combination of two or more of a non-polar organic solvent and a low-polar organic solvent.
6. The method for preparing a super hydrophobic material according to claim 1, wherein The volume ratio of the organic solvent to the poor solvent is 1:5-50.
7. The method for preparing a super hydrophobic material according to claim 1, wherein The poor solvent is selected from one or a combination of two or more highly polar solvents.
8. The method for preparing a super hydrophobic material according to claim 1, wherein The olefin polymer resin contains 0.5-5% of polysiloxane by weight of the olefin polymer resin.
9. The method for preparing a super-hydrophobic material according to claim 8, wherein The structure of the polysiloxane is shown in the following formula (1): R 1 Me2SiO(SiOMe2) x (SioMeR 2 ) y SiMe2R 3 (1) Among them, R 1 , R 2 and R 3 independently selected from C1-C18 alkyl, Me represents methyl, x≥0, y≥0, 5≤x+y≤100.
10. A super hydrophobic material, characterized in that: The super-hydrophobic material is prepared by the preparation method of the super-hydrophobic material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for realizing super-hydrophobic modification of polypropylene material
CN115522387A